Degradative and Non-Degradative Roles of Autophagy Proteins in Metabolism and Metabolic Diseases - Kuramoto, Kenta; He, Congcong (Frontiers in Cell and Developmental Biology, 2022)
Autophagy is a stress-induced lysosomal degradation pathway regulated by evolutionarily conserved autophagy-related (ATG) genes. Recent research has revealed that autophagy plays an important role in the regulation of energy metabolism, development of metabolic tissues, and pathogenesis of metabolic disorders. Bulk and selective degradation by autophagy helps maintain protein homeostasis and physiological function of cells. Aside from classical degradative roles, ATG proteins also carry out non-classical secretory functions of metabolic tissues. In this review, we summarize recent progresses and unanswered questions on the mechanisms of autophagy and ATG proteins in metabolic regulation, with a focus on organelle and nutrient storage degradation, as well as vesicular and hormonal secretion. Such knowledge broadens our understanding on the cause, pathophysiology, and prevention of metabolic diseases including obesity and diabetes.